Value of urinary kidney injury molecule-1 levels in predicting acute kidney injury in very low birth weight preterm infants. Issue 12 (December 2020) - Unal, Ebru Turkoglu; Ozer, Esra Arun; Kahramaner, Zelal; Erdemir, Aydin; Cosar, Hese; Sutcuoglu, Sumer
Objective: This study aimed to evaluate the significance of urinary kidney injury molecule-1 (uKIM-1) levels in predicting acute kidney injury (AKI) and mortality in very low birth weight (VLBW) preterm infants. Methods: This prospective, observational cohort study was conducted on 39 VLBW preterm infants. Serum creatinine (SCr) and uKIM-1 levels were measured in the first 24 and 48 to 72 hours of life. The estimated glomerular filtration rate (eGFR) was calculated. Levels of uKIM-1 were measured with an enzyme-linked immunosorbent assay. Results: Among 39 VLBW infants, 9 (23%) developed AKI. The mortality rate was 17.9% (n = 7 neonates). There was no significant difference in SCr levels, uKIM-1 levels, or the eGFR obtained in the first 24 hours in the AKI group compared with controls. However, significant differences were found in SCr and uKIM-1 levels, and the eGFR rate at 48 to 72 hours between the groups. Levels of uKIM-1 were significantly higher in non-survivors than in survivors in the first 24 and 48 to 72 hours of life. Conclusion: The level of uKIM-1 can be used as a simple noninvasive diagnostic method for predicting AKI and mortality, especially within 48 to 72 hours of life. Clinical trial registration: We do not have a clinical trial registration ID. In Turkey, clinical trial registration is not required for non-drug, noninvasive, clinical studies.